Fire force. 05 - Ōkubo, Atsushi (Kodansha Comics, 2017)
"Shinra has learned that his brother is not only alive, he's working for the enemy! Will Company 8's strong sense of justice turn Shinra against his own family? Learn the story of how Company 8 was formed and follow their exploits as they confront the unconventional Company 7 in their quest to find the Evangelist"--Pg.4 of cover.